Fibroin-MXene composite film and preparation method thereof

By using a three-layer gradient structure of silk protein-MXene composite film, the problems of insufficient performance synergy, poor stability and weak interfacial bonding of existing films are solved, achieving high conductivity and excellent mechanical properties, making it suitable for flexible electronics and electromagnetic protection.

CN121083997APending Publication Date: 2025-12-09龙雪
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511153513.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing MXene-natural polymer composite films suffer from insufficient performance synergy, poor MXene stability, and weak interfacial bonding.

Method used

A three-layer gradient structure silk fibroin-MXene composite film is constructed. The conductive surface layer consists of oriented MXene nanosheets and silk fibroin, the porous responsive layer consists of silk fibroin-MXene freeze-dried sponge, and the supporting bottom layer consists of cross-linked silk fibroin. Through electrospinning, freeze-drying, and cross-linking treatment, combined with Ca2+ solution infiltration cross-linking and stretching treatment, the interfacial bonding and stability are improved.

Benefits of technology

It achieves high conductivity, excellent mechanical properties and environmental responsiveness, improves the structural stability and interfacial bonding of the material, solves the performance contradictions of traditional composite films, and is suitable for flexible electronics and electromagnetic protection fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a silk protein-MXene composite film and a preparation method thereof. The silk protein-MXene composite film sequentially comprises a conductive surface layer, a porous response layer and a supporting bottom layer from top to bottom, the invention relates to the technical field of composite films. According to the fibroin-MXene composite film and the preparation method thereof, a three-layer gradient structure is formed by the conductive surface layer, the porous response layer and the supporting bottom layer, good conductivity and electromagnetic shielding effectiveness are ensured by utilizing oriented arrangement of MXene of the conductive surface layer, gallic acid and MXene form a hydrogen bond network, and nitrogen-doped carbon quantum dots coat the surface of MXene to form a physical barrier, so that the electromagnetic shielding effect is improved, and the electromagnetic shielding effect is improved. Through double oxidation resistance of gallic acid and nitrogen-doped carbon quantum dots, a sponge body structure formed by the porous response layer is matched to endow the composite film with high-sensitivity response to external stimulation, the supporting bottom layer is crosslinked by hexamethylene diisocyanate and enhanced by nanocellulose, the tensile strength is improved, and the tensile strength of the composite film is improved. And the contradiction between the mechanical property and the conductivity of the traditional composite film is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite film technology, specifically to a silk fibroin-MXene composite film and its preparation method. Background Technology

[0002] With the rapid development of flexible electronics, smart wearables, and electromagnetic protection, the demand for composite thin film materials that combine high conductivity, excellent mechanical properties, environmental responsiveness, and biocompatibility is becoming increasingly urgent. Two-dimensional transition metal carbides / nitrides (MXenes) have become ideal candidates for preparing conductive functional materials due to their ultra-high conductivity and good flexibility; while silk fibroin (especially silk protein), as a natural polymer material, has excellent biocompatibility, biodegradability, and good mechanical properties. The active groups in its molecular chain (such as hydroxyl and amino groups) can also be chemically modified to achieve functional regulation. The combination of the two is expected to achieve complementary properties.

[0003] However, existing MXene-natural polymer composite films have the following drawbacks: 1) Insufficient performance synergy: Single structural design makes it difficult to balance conductivity and mechanical properties. For example, excessive MXene content can lead to increased film brittleness, while excessive natural polymer content can significantly reduce conductivity. 2) Poor stability of MXene: MXene nanosheets are easily oxidized in air, which leads to a decrease in conductivity over time, especially under high temperature and high humidity conditions. 3) Weak interfacial bonding: The interaction between MXene and natural polymers is mostly physical, with low interfacial shear strength, making it prone to interlayer delamination under stress or environmental changes.

[0004] In view of this, a silk fibroin-MXene composite film and its preparation method are proposed. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a silk fibroin-MXene composite film and its preparation method, which solves the problems of insufficient performance synergy, poor MXene stability, and weak interfacial bonding in existing MXene-natural polymer composite films.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a silk fibroin-MXene composite film, comprising, from top to bottom: A conductive surface layer, wherein the conductive surface layer is formed by electrospinning and oriented arrangement of MXene nanosheets and silk fibroin; A porous responsive layer, wherein the porous responsive layer is composed of a silk fibroin-MXene freeze-dried sponge; The supporting substrate is composed of silk fibroin cross-linked with hexamethylene diisocyanate; The thickness ratio of the conductive surface layer, the porous response layer, and the support substrate is 5-15:20-60:10-20.

[0007] The present invention is further configured such that the conductive surface layer contains MXone and silk fibroin in a mass ratio of 1:3-5.

[0008] The present invention is further configured such that the method for preparing the conductive surface layer includes: MXone was dispersed in dimethylformamide solution to obtain an MXone dispersion of 18 mg / mL. Regenerated silk fibroin was dispersed in deionized water to obtain a regenerated silk fibroin solution with a concentration of 8 wt%. 0.8 wt% gallic acid and 0.3 wt% nitrogen-doped carbon quantum dots were added to the MXone dispersion and sonicated for 30 min. Then it was mixed with the regenerated silk fibroin solution. Degummed waste silk was dissolved in 9.3 mol / L LiBr solution. After dialyzing, the concentration of silk fibroin was adjusted to 15–25 wt%. Electrospinning was performed with a voltage of 15–25 kV, a receiving distance of 10–15 cm, and a fiber diameter of 100–500 nm.

[0009] The present invention is further configured such that the MXone and silk fibroin in the porous response layer are in a mass ratio of 1:3-5.

[0010] The present invention is further configured such that the method for preparing the porous response layer includes: After mixing the MXone dispersion and silk fibroin solution, add 0.1-0.5 wt% of ammonium bicarbonate and stir magnetically at 200 rpm for 1 h. Degas under vacuum at -0.1 MPa for 30 min, pre-freeze at -20℃ for 2 h, freeze-dry at -50℃ for 24 h, then sublimate and dry at -40℃ under 10 Pa vacuum for 10 h, and finally sublimate and dry at 25℃ under 1 Pa vacuum for 8 h.

[0011] The present invention is further configured such that the hexamethylene diisocyanate and silk fibroin in the supporting bottom layer comprise a mass ratio of 100:2-5.

[0012] The present invention is further configured such that the method for preparing the supporting substrate includes: After reacting hexamethylene diisocyanate and silk fibroin solution at 60℃ for 30 min, 0.5 wt% nanocellulose was added, mixed evenly, cast, cured at 40℃ for 12 h, and then cured at 80℃ for 2 h.

[0013] This invention also discloses a method for preparing a silk fibroin-MXene composite film, comprising: The support layer, porous response layer, and conductive surface layer are stacked sequentially from bottom to top. Under a pressure of 0.5–1 MPa, and after passing through a concentration of 0.1–0.5 mol / L Ca... 2+ The solution is permeated and crosslinked for 10–30 min, then stretched at a stretch ratio of 250%–300%, and then set at 70°C to obtain a silk fibroin-MXene composite film.

[0014] This invention provides a silk fibroin-MXene composite film and its preparation method. It has the following beneficial effects: (1) The present invention forms a three-layer gradient structure consisting of a conductive surface layer, a porous response layer and a support bottom layer. The directional arrangement of MXene in the conductive surface layer ensures good electrical conductivity and electromagnetic shielding effectiveness. Gallic acid forms a hydrogen bond network with MXene. Nitrogen-doped carbon quantum dots coat the surface of MXene to form a physical barrier. The dual antioxidant properties of gallic acid and nitrogen-doped carbon quantum dots, combined with the sponge structure formed by the porous response layer, give the composite film a high sensitivity response to external stimuli. The support bottom layer is cross-linked with hexamethylene diisocyanate and reinforced with nanocellulose to improve tensile strength, effectively solving the contradiction between mechanical properties and conductivity of traditional composite films.

[0015] (2) This invention ensures component continuity at the interface and reduces electrical signal transmission loss by maintaining a consistent mass ratio of MXene and silk fibroin between the conductive surface layer and the porous response layer; through Ca 2+ Solution infiltration crosslinking and stretching treatment enhance interlayer bonding, prevent interlayer delamination during use, and effectively improve the structural stability of the material. Detailed Implementation

[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] The embodiments of the present invention provide the following technical solutions: Example 1 A method for preparing a silk fibroin-MXene composite film includes the following steps: S1, Preparation of conductive surface layer MXene was dispersed in dimethylformamide solution to prepare an MXene dispersion with a concentration of 18 mg / mL. Degummed waste silk was dissolved in 9.3 mol / L LiBr solution, dialyzed, and the concentration of regenerated silk fibroin was adjusted to 15 wt%. The above MXene dispersion and silk fibroin solution were mixed at a MXene to silk fibroin ratio of 1:3. 0.8 wt% gallic acid and 0.3 wt% nitrogen-doped carbon quantum dots were added to the mixture, and it was ultrasonically treated for 30 min. Oriented fibers were prepared by electrospinning with the following parameters: voltage 15kV, receiving distance 10cm, resulting in a conductive surface layer with a fiber diameter of 100-200nm and a thickness of 5μm. S2, Preparation of porous response layer At a MXene to silk fibroin mass ratio of 1:3, 18 mg / mL MXene dispersion was mixed with 15 wt% silk fibroin solution, and 0.1 wt% ammonium bicarbonate was added. The mixture was magnetically stirred at 200 rpm for 1 h and then degassed under vacuum at -0.1 MPa for 30 min. The mixture was pre-frozen at -20℃ for 2 h, then freeze-dried at -50℃ for 24 h, and then sublimated under 10 Pa vacuum at -40℃ for 10 h, and then sublimated under 1 Pa vacuum at 25℃ for 8 h to obtain a porous responsive layer with a thickness of 20 μm. S3, Support Substrate Preparation The silk fibroin and hexamethylene diisocyanate were reacted at 60°C for 30 min according to a mass ratio of 100:2. Then, 0.5 wt% nanocellulose was added and mixed evenly. After casting into a film, it was cured at 40°C for 12 h and then cured at 80°C for 2 h to obtain a support layer with a thickness of 10 μm. S4, Composite film molding A support layer, a porous response layer, and a conductive surface layer are stacked sequentially from bottom to top. Under a pressure of 0.5 MPa, and after passing through a 0.1 mol / L Ca solution... 2+ Solution permeation crosslinking for 30 min, stretching treatment at a 250% stretch ratio, and finally setting at 70℃ yielded a silk fibroin-MXene composite film, in which Ca... 2+ The solution used is calcium chloride solution.

[0018] In this embodiment, the silk fibroin-MXene composite film has a conductivity of 580 S / m, a tensile strength of 82 MPa, a pressure response time of 45 ms, and stable response sensitivity within a humidity range of 30% to 90% RH.

[0019] Example 2 S1, Preparation of conductive surface layer The concentration of MXene dispersion and the preparation of silk fibroin solution were the same as in Example 1, with MXene and silk fibroin mixed at a mass ratio of 1:4. Gallic acid and nitrogen-doped carbon quantum dots were added in the same proportion, followed by ultrasonic treatment. The electrospinning parameters were adjusted as follows: voltage 20kV, receiving distance 12cm, fiber diameter 300-400nm, and conductive surface layer thickness 10μm. S2, Preparation of porous response layer The MXene and silk fibroin were mixed at a ratio of 1:4, and the amount of ammonium bicarbonate added was 0.3 wt% of the total mass. The rest of the freeze-drying and sublimation drying processes were the same as in Example 1. The thickness of the porous response layer was 40 μm. S3, Support Substrate Preparation The reaction was carried out with silk fibroin and hexamethylene diisocyanate at a mass ratio of 100:3.5, with the amount of nanocellulose added and the curing process remaining unchanged, and the thickness of the support substrate was 15μm. S4, Composite film molding After being stacked between layers, the mixture was subjected to a pressure of 0.8 MPa and a concentration of 0.3 mol / L Ca. 2+ Solution permeation crosslinking for 20 minutes, stretch ratio 275%, set at 70℃; In this embodiment, the silk fibroin-MXene composite film has a conductivity of 620 S / m, a tensile strength of 105 MPa, a pressure response time of 40 ms, and a mechanical property retention rate of over 90% in an environment ranging from -20℃ to 80℃.

[0020] Example 3 The difference between this embodiment and Embodiment 1 is that: S1, Preparation of conductive surface layer The MXene and silk fibroin were mixed at a ratio of 1:5. The electrospinning parameters were: voltage 25kV, receiving distance 15cm, fiber diameter 400-500nm, and conductive surface layer thickness 15μm. S2, Preparation of porous response layer The mixture of MXene and silk fibroin was prepared at a ratio of 1:5, with ammonium bicarbonate added at a total mass of 0.5 wt%, and the porous response layer was 60 μm thick. S3, Support Substrate Preparation The reaction was carried out with silk fibroin and hexamethylene diisocyanate at a mass ratio of 100:5, and the thickness of the support substrate was 20μm. S4, Composite film molding At a pressure of 1 MPa, after passing through a 0.5 mol / L Ca 2+ Solution permeation crosslinking for 10 min, stretching ratio 300%, and setting at 70℃.

[0021] In this embodiment, the silk fibroin-MXene composite film has a conductivity of 550 S / m, a tensile strength of 118 MPa, and a cell viability of 96.5%, making it suitable for wearable devices that require long-term skin contact.

[0022] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A silk fibroin-MXene composite film, characterized in that, From top to bottom, they include: A conductive surface layer, wherein the conductive surface layer is formed by electrospinning and oriented arrangement of MXene nanosheets and silk fibroin; A porous responsive layer, wherein the porous responsive layer is composed of a silk fibroin-MXene freeze-dried sponge; The supporting substrate is composed of silk fibroin cross-linked with hexamethylene diisocyanate; The thickness ratio of the conductive surface layer, the porous response layer, and the support substrate is 5-15:20-60:10-20.

2. The silk fibroin-MXene composite film according to claim 1, characterized in that, The conductive surface layer contains MXone and silk fibroin in a mass ratio of 1:3-5.

3. The silk fibroin-MXene composite film according to claim 2, characterized in that, The method for preparing the conductive surface layer includes: MXone was dispersed in dimethylformamide solution to obtain an MXone dispersion of 18 mg / mL. Regenerated silk fibroin was dispersed in deionized water to obtain a regenerated silk fibroin solution with a concentration of 8 wt%. 0.8 wt% gallic acid and 0.3 wt% nitrogen-doped carbon quantum dots were added to the MXone dispersion and sonicated for 30 min. Then it was mixed with the regenerated silk fibroin solution. Degummed waste silk was dissolved in 9.3 mol / L LiBr solution. After dialyzing, the concentration of silk fibroin was adjusted to 15–25 wt%. Electrospinning was performed with a voltage of 15–25 kV, a receiving distance of 10–15 cm, and a fiber diameter of 100–500 nm.

4. The silk fibroin-MXene composite film according to claim 3, characterized in that, The porous responsive layer contains MXone and silk fibroin in a mass ratio of 1:3-5.

5. The silk fibroin-MXene composite film according to claim 4, characterized in that, The method for preparing the porous responsive layer includes: After mixing the MXone dispersion and silk fibroin solution, add 0.1-0.5 wt% of ammonium bicarbonate and stir magnetically at 200 rpm for 1 h. Degas under vacuum at -0.1 MPa for 30 min, pre-freeze at -20℃ for 2 h, freeze-dry at -50℃ for 24 h, then sublimate and dry at -40℃ under 10 Pa vacuum for 10 h, and finally sublimate and dry at 25℃ under 1 Pa vacuum for 8 h.

6. The silk fibroin-MXene composite film according to claim 3, characterized in that, The hexamethylene diisocyanate and silk fibroin in the supporting bottom layer are in a mass ratio of 100:2-5.

7. The silk fibroin-MXene composite film according to claim 6, characterized in that, The method for preparing the supporting substrate includes: After reacting hexamethylene diisocyanate and silk fibroin solution at 60℃ for 30 min, 0.5 wt% nanocellulose was added, mixed evenly, cast, cured at 40℃ for 12 h, and then cured at 80℃ for 2 h.

8. A method for preparing a silk fibroin-MXene composite film, characterized in that, include: The support layer, porous response layer, and conductive surface layer are stacked sequentially from bottom to top. Under a pressure of 0.5–1 MPa, and after passing through a concentration of 0.1–0.5 mol / L Ca... 2+ The solution is permeated and crosslinked for 10–30 min, then stretched at a stretch ratio of 250%–300%, and then set at 70°C to obtain a silk fibroin-MXene composite film.

Citation Information

Cited By

  • MXene / wool keratin electrode and preparation method and application thereof

    CN121973507A

  • MXene / wool keratin electrode and preparation method and application thereof

    CN121973507B